Frequency‐dependent NMR relaxation of liquids confined inside porous media containing an increased amount of magnetic impurities. (10th January 2013) - Muncaci, Sergiu; Mattea, Carlos; Stapf, Siegfried; Ardelean, Ioan
<x xml:space="preserve">Abstract</x> Frequency‐dependent NMR relaxation studies have been carried out on water (polar) and cyclohexane (nonpolar) molecules confined inside porous ceramics containing variable amounts of iron oxide (III). The porous ceramics were prepared by compression of powders mixed with iron oxide followed by thermal treatment. The pore size distribution was estimated using a technique based on diffusion in internal fields that exposed a narrow distribution of macropore sizes with an average pore dimension independent of iron oxide content. The relaxation dispersion curves were obtained at room temperature using a fast field cycling NMR instrument. They display an increase of the relaxation rate proportional to the iron oxide concentration. This behavior is more prominent at low Larmor frequencies and is independent of the polar character of the confined molecules. The results reported here can be fitted well with a relaxation model considering exchange between molecules in the close vicinity of the paramagnetic centers located in the surface and bulk‐like molecules inside the pores. This model allows the extraction of the transverse diffusional correlation time that can be related to the polar character of the confined molecules. Copyright © 2013 John Wiley & Sons, Ltd.